Constructing Gender Consciousness through TikTok: A Social Representational Analysis of Patriarchal Culture in Indonesia - Mutiara Lestari; Iman Sumarlan (Electronic Journal of Education, Social Economics and Technology, 2026)
The expansion of digital media has reshaped how social issues are articulated and negotiated in everyday life, including questions of gender and power. This study examines how gender consciousness is constructed through TikTok content by analyzing social representations of patriarchal culture on the Indonesian TikTok account @bincangperempuan. Employing a qualitative research approach, the study analyzes eight TikTok videos published between January and June 2025 using purposive sampling. Data were collected through content documentation and observation, focusing on narrative, visual, and discursive elements, and were analyzed using qualitative descriptive analysis. The findings indicate that patriarchal culture is predominantly represented through women’s everyday lived experiences rather than abstract or institutional discourse. Personal storytelling, dialogic communication, and audiovisual strategies function as key mechanisms in transforming individual experiences into shared social meanings. Audience interaction further extends this process by fostering collective reflection and reinforcing gender awareness through participatory dialogue. The study demonstrates that gender consciousness emerges as a socially mediated and gradual process, shaped through representation, interaction, and symbolic interpretation. Overall, the findings highlight TikTok’s role as a social space that facilitates the articulation of gender awareness and symbolic resistance to patriarchal norms within contemporary Indonesian society.